1213. Evaluation of an Alcohol-Based Antiseptic for Nasal Decolonization of Methicillin-Resistant Staphylococcus aureus (MRSA). (26th November 2018) - Kanwar, Anubhav; Cadnum, Jennifer L; Mana, Thriveen Sankar Chittoor; Gestrich, Scott; Jencson, Annette; Donskey, Curtis J
Abstract: Background: Due to concerns for emergence of mupirocin resistance, there is an interest in use of topical antiseptics for nasal decolonization of Staphylococcus aureus . Alcohol-based nasal antiseptics have recently been developed as an alternative to mupirocin, but there is limited data on efficacy, particularly among patients where the burden of carriage is often high. Methods: We evaluated the effectiveness of a one-time application of a commercial alcohol-based nasal sanitizer for reduction in nasal methicillin-resistant Staphylococcus aureus (MRSA) in MRSA-colonized patients. Patients received either a single dose or triple dose over 3 minutes; the triple dose is recommended for preoperative dosing. Swabs were used for quantitative culture of MRSA from the anterior nares and vestibule prior to and 10 minutes, 2 hours, and 6 hours after application. For a subset of patients, cultures for MRSA were collected from hands, clothing, groin, and chest/axilla. Results: Of 34 MRSA carriers enrolled, 27 (79%) had MRSA detected in nares, 32 (94%) were male, and the mean age was 65. Of the 27 carriers positive for nasal MRSA, 15 (56%) received a single alcohol dose and 12 (44%) received a triple dose over 3 minutes. As shown in the figure, the single and triple dose applications significantly reduced MRSA concentrations at 2 hours post-treatment when the initial burden was low (i.e., <2 log10 colonies per swab), but there was no significant reduction at 6 hours; there was no significant reduction with either dose when the initial burden was high (≥2 log10 colonies per swab). Conclusion: A single application of an alcohol nasal sanitizer significantly reduced nasal MRSA at 2 hours post-application when the initial burden of colonization was low, but not when a high burden of carriage was present. Additional studies are needed to determine whether higher alcohol doses or repeated applications might result in improved efficacy. Disclosures: All authors: No reported disclosures.